Elevated Thrombin Generation and Venous Thromboembolism Incidence in Patients Undergoing Cytoreductive Surgery with Hyperthermic Intraperitoneal Chemotherapy Compared with Minimally Invasive Rectal Surgery - Lundbech, Mikkel; Krag, Andreas E.; Iversen, Lene H.; Brandsborg, Birgitte; Madsen, Nina; Hvas, Anne-Mette (Thrombosis and Haemostasis, 2024)
Surgical treatment of colorectal cancer carries a risk for venous thromboembolism (VTE). We investigated changes in coagulation and fibrinolysis and the VTE incidence within 30 days in patients undergoing open cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS + HIPEC) for peritoneal metastases from colorectal cancer and minimally invasive surgery (MIS) for localized rectal cancer.This cohort study included 45 CRS + HIPEC and 45 MIS patients. Blood samples were obtained preoperatively, at the end of surgery, and postoperative day (POD) 1, 3 to 4, and 5 to 7. Systematic ultrasonographic screening for VTE was performed between POD 3 and 7. Computed tomography scan was performed if complications were suspected. The primary endpoint was the difference in mean change (Δ) with [95% confidence intervals] from preoperative to end of surgery in prothrombin fragment 1 + 2 (F1 + 2) levels. Secondary endpoints were the difference in mean change in biomarkers of coagulation and fibrinolysis from preoperative to POD 5 to 7 and the VTE incidence.F1 + 2 levels increased from preoperative to the end of surgery in both groups. The mean increase from preoperative to end of surgery in F1 + 2 levels was significantly greater in CRS + HIPEC patients than MIS patients: Δ1,322 [1,040:1,604] pmol/L, p < 0.01. The VTE incidence was significantly higher after CRS + HIPEC than MIS (24 vs. 5%, p = 0.01).F1 + 2 levels were increased after both procedures, but to a far greater extent following CRS + HIPEC. The VTE incidence within 30 days was significantly higher in patients treated with CRS + HIPEC than in MIS patients.
Keywords: blood coagulation; coagulation; hyperthermic intraperitoneal chemotherapy; neoplasms; surgical procedures; operative; cytoreductive surgery; minimally invasive surgical procedures